Development and kinetic evaluation of PLA/NCC nanofilms: A comparative study of gelatin and starch for effective drug delivery system - Ayuni Nazurah, Salim Salmi; Norhayati, Abdullah; Noryn Haniz, Sa’adin; Nur Amirah, Mohamed Salpini; Syed, Murtaza Haider (Trans Tech Publications, Switzerland, 2025)
Conventional drug delivery systems face challenges like low bioavailability, rapid degradation and limited effectiveness in drug delivery, especially for persistent infections. Our research focus to develop nanofiber drug delivery systems (NDDSs) using biopolymers like starch and gelatine. In this study, nanofilm was produced using polylactic acid (PLA), Nanocrystalline Cellulose (NCC), gelatine/starch, and paracetamol (acetaminophen) as the drug at different ratios. From SEM, the best ratio for gelatine-based nanofilm was 6% PLA: 0.5% gelatine : 0.15% NCC : 0.02% drug while starch-based nanofilm the best ratio was 8% PLA: 0.2% starch: 0.15% NCC: 0.02% drug. In drug release kinetics study, the results were compared using mathematical models such as zero order, first order, and Higuchi models for both types of bio-based nanofilm. The drug release kinetics results indicate that the starch-based nanofilm was superior to the gelatin-based nanofilm in drug delivery, fitting both the Higuchi and Zero-order models.